Current efforts and challenges facing responses to 2019-nCoV in Africa - Don Eliseo Lucero-Prisno; Yusuff Adebayo Adebisi; Xu Lin (BMC, 2020)
Abstract The novel coronavirus is a pandemic that has started to creep into Africa thus making the virus a truly global, health security threat. The number of new 2019-nCoV cases has been rising in Africa, though currently lower than the cases reported outside the region. African countries have activated their Emergency Operations Centres to coordinate responses and preparedness activities to the pandemic. A series of measures such as restricting travel, case detection and contact tracing, mandatory quarantine, guidance and information to the public among other efforts are being implemented across Africa. However, the presence of porous borders, the double burden of communicable and non-communicable diseases, poverty, poor health literacy, infodemic and family clustering, and most of all, weak health systems, may make containment challenging. It is important for African countries to continue to intensify efforts and address the challenges to effectively respond to the uncertainty the pandemic poses.